2021
DOI: 10.1186/s12864-021-07968-6
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast genome of Amygdalus L. (Rosaceae) reveals the phylogenetic relationship and divergence time

Abstract: Background Limited access to genetic information has greatly hindered our understanding of the molecular evolution, phylogeny, and differentiation time of subg. Amygdalus. This study reported complete chloroplast (cp) genome sequences of subg. Amygdalus, which further enriched the available valuable resources of complete cp genomes of higher plants and deepened our understanding of the divergence time and phylogenetic relationships of subg. Amygdalus. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…Thus, it is highly conserved in structure and gene composition. Based on these characteristics, chloroplast genome sequence data should provide robust solutions for studies on phylogenetics, molecular evolution, population genetics, and phylogeography ( Dong et al, 2013 ; Yang et al, 2020 , 2021b ; Du et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is highly conserved in structure and gene composition. Based on these characteristics, chloroplast genome sequence data should provide robust solutions for studies on phylogenetics, molecular evolution, population genetics, and phylogeography ( Dong et al, 2013 ; Yang et al, 2020 , 2021b ; Du et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chloroplast (cp) is an organelle in plants and algae ( Du et al, 2021 ; Li et al, 2021 ) that plays a significant role in plant cell function, including in photosynthesis, carbon fixation, and stress response. The cp is a semiautonomous organelle with a relatively independent genome containing its own genetic system for replication, transcription, and translation ( Favier et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of 20 Indigofera plastomes revealed that rp s19, ycf 1, and ndh F demonstrated pronounced expansion or contraction, as reported in Salvia L., Amygdalus L., Iris L., Prunus L. subg. Cerasus Mill., and Asteraceae ( Du et al., 2021 ; Pascual-Diaz et al., 2021 ; Du et al., 2022 ; Feng et al., 2022a ; Li et al., 2022c ). These subtle differences in boundaries could potentially be used for species identification.…”
Section: Discussionmentioning
confidence: 99%